Terapi Cognitif-Behavioral untuk Modifikasi Core Belief antara Pasangan dalam Pernikahan - Agus Handini (Raheema, 2014)
There are two factors causing an anxiety to women, the internal and external factors. Furthermore, the internal factor includes women’s role in a domestic matter. Linda Hager says the unfinished pressure for women isto manage their schedule towards the children, society, religious life, and work’s responsibility. Those, according to Hager, lead to overload or hot reactor behavior(Hager & Hager, 1999:24). Moreover, the external factor is women’s self-devotion towards their couple and children that cuts off their own time for themselves. As a result, the women will experience the loneliness, anger, and frustration because of their life choices (Hager & Hager, 1999:24). Therefore, the honeymoon effects will be terminated due to those situation and preferences.